Notes on the state-society relations in Paraná: a brief digression for the 1853-1965 period - Macedo, Mariano de Matos (2011)
The development process of the brazilian capitalism during the 20th century operated, essentially, based on the interrelationship between economy, society and state, in a continuous politicalstructuring movement, and in straight connection with the predominating economic concerns of each period of time.